Application of the Earned Value Analysis (EVA) Method to Assess Performance Costs and Time in Campus X Lecture Building - Yusuf, Ahmad Sirozuddin; Tantri, Diana; Yuda Saputra, Adam; Budisiswanto, Nurullah; Marantica, Lutfi (International Journal of Social Service and Research, 2025)
Rapid economic growth has driven increased infrastructure development, including the construction of lecture halls. In the implementation of construction projects, deviations between plans and actual outcomes are often encountered, both in terms of cost and time. This research aims to evaluate the cost and time performance of the construction project for the Academic Building at Campus X using the Earned Value Analysis (EVA) method. This study uses a descriptive quantitative approach. Data were collected from project documents such as the Bill of Quantities (BoQ), Project Implementation Plan (PIP), time schedule, and monthly reports. Performance indicators, such as the Schedule Performance Index (SPI) and Cost Performance Index (CPI), were analyzed to evaluate time and cost efficiency. The analysis results show that the project is cost-efficient, with the CPI value consistently above 1, peaking at 1.382. Time performance is relatively good, although there were minor delays in the 4th and 11th months, with the SPI value ranging from 0.96 to 2.72. The project was successfully completed within 12 months as originally planned. The final cost estimate (Estimate at Completion) of Rp 28,433,930,871.17 was lower than the initial budget (Budget at Completion) of Rp 33,793,610,189.25, resulting in an efficiency of 15.86%. This research concludes that EVA is an effective tool for quantitatively evaluating project performance, providing a clear picture of cost and time deviations, and can serve as a reference for project managers in making strategic decisions.